First in situ evidence of electron pitch angle scattering due to magnetic field line curvature in the Ion diffusion region. Issue 5 (7th May 2016) - Zhang, Y. C.; Shen, C.; Marchaudon, A.; Rong, Z. J.; Lavraud, B.; Fazakerley, A.; Yao, Z.; Mihaljcic, B.; Ji, Y.; Ma, Y. H.; Liu, Z. X.
Abstract: Theory predicts that the first adiabatic invariant of a charged particle may be violated in a region of highly curved field lines, leading to significant pitch angle scattering for particles whose gyroradius are comparable to the radius of the magnetic field line curvature. This scattering generates more isotropic particle distribution functions, with important impacts on the presence or absence of plasma instabilities. Using magnetic curvature analysis based on multipoint Cluster spacecraft observations, we present the first investigation of magnetic curvature in the vicinity of an ion diffusion region where reconnected field lines are highly curved. Electrons at energies > 8 keV show a clear pitch angle ordering between bidirectional and trapped distribution in surrounding regions, while we show that in the more central part of the ion diffusion region electrons above such energies become isotropic. By contrast, colder electrons ( 1 keV) retain their bidirectional character throughout the diffusion regions. The calculated adiabatic parameter K 2 for these electrons is in agreement with theory. This study provides the first observational evidence for particle pitch angle scattering due to magnetic field lines with well characterized curvature in a space plasma. Key Points: First multispacecraft analysis of magnetic field curvature in the ion diffusion region Electron dynamics is analyzed as a function of magnetic field curvature Observational evidence for magnetic curvature‐induced electron pitch angle scattering